1994
DOI: 10.1002/chin.199448193
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Characterization of 1,2,3‐Triphospholide Anions.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In contrast, A and B (Scheme 2) were obtained at room temperature in our previous study 2 Hz], 8 the particularly high chemical shift observed for P(2) compared to other 1,2,3-phospholide anions is worthy of note. 8,9 This chemical shift is similar to that found in [(RN) 2 P] À ligands, which also contain two-coordinate P III . 10 Surprisingly, bearing in mind the greater electronegativity of N compared to P, the 13 C chemical shift of the quaternary carbon atoms in the anion of 1 (d = 173.1) is significantly higher than that found in the benzo-triazolyl anion of [C 6 H 4 N 3 LiÁ2DMSO] N (d = 145.3 11 ).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, A and B (Scheme 2) were obtained at room temperature in our previous study 2 Hz], 8 the particularly high chemical shift observed for P(2) compared to other 1,2,3-phospholide anions is worthy of note. 8,9 This chemical shift is similar to that found in [(RN) 2 P] À ligands, which also contain two-coordinate P III . 10 Surprisingly, bearing in mind the greater electronegativity of N compared to P, the 13 C chemical shift of the quaternary carbon atoms in the anion of 1 (d = 173.1) is significantly higher than that found in the benzo-triazolyl anion of [C 6 H 4 N 3 LiÁ2DMSO] N (d = 145.3 11 ).…”
supporting
confidence: 76%
“…13 However, although the chemistry of 1,3,4-triphospholide ions is well developed, far less is known about the chemistry of 1,2,3-triphospholides and there is no simple route to the 1,2,3phospholide framework. 14 For example, the parent ion 1,2,3-[(CH) 2 P 3 ] À can only be obtained as a mixture with [(CH)P 4 ] À from the thermolysis of P 4 and Na in diglyme, 8 and the 1,2,3-[(PhC) 2 P 3 ] À ligand can only be obtained either from a multistep synthesis 9 or via reaction at a transition metal centre. 15 The importance of obtaining 1 is that it provides a very ready crystalline source of the 1,2,3-benzo-phospholide anion, which is the first phospholide analogue of the indenyl anion [C 6 H 4 (CH) 3 ] À .…”
mentioning
confidence: 99%
“…Until very recently there were only three reported examples of reactions giving rise to 1,2,3-[P 3 C 2 R 2 ] À type systems, all of which exhibit significant limitations on the nature and quantities of the triphospholides produced. [5][6][7] More recently two coterminous reports providing a rational synthesis to the 1,2,3triphospha-indenyl anion were reported. 8,9 However, despite these advances there are still significant obstacles facing the synthesis of 1,2,3-triphospholide systems.…”
mentioning
confidence: 99%
“…Bond metric parameters for 1 are consistent with other literaturereported values for related systems. [6][7][8][9] The [K(2,2,2-crypt)] + and [K(18-crown-6)] + salts of 2 exhibit discreet and continuous positional disorder of the 1,2,3-triarsalide moieties, respectively. As a result a detailed analysis of bond metric data is not advisable; however the composition and connectivity of the anion are unequivocal.…”
mentioning
confidence: 99%
“…Although preparations of 1,2,3-triphospholide anions, [R 2 C 2 P 3 ] À , have been previously reported, [14][15][16] the synthetic protocols all have their limitations, either being complicated multistep procedures or not giving access to the anionic reagent; moreover, they cannot be extended to provide access to the [1,2,3-C 6 H 4 P 3 ] À anion of 1. The synthetic protocol described in this paper has the advantages of being rapid (preparation time of ca.…”
mentioning
confidence: 99%